THE SIGNIFICANCE OF THE SENTINEL LYMPH NODE IN COLORECTAL CANCER AND ITS ISOLATION WITH RADIOACTIVE COLLOID-A PILOT STUDY - Antovikj, Svetozar; Jankulovski, Nikola; Stojanoski, Sinisha (Македонско лекарско друштво = Macedonian medical association/De Gruyter, 2014)
Introduction. One of the most important factors for prognosis in patients with colorectal cancer (CRC), especially the 5-year survival is the status of regional lymph nodes (RLN). Threfore, today’s recommendations for systematic lymphadenectomy in CRC operations are very important. For correct staging and accepted by all international recommendations, at least 12 LN must be analyzed microscopically. The sentinel lymph node (SLN) is the first lymph node that drains lymph from the tumor and thus represents a LN that has the greatest chance to be the bearer of metastatic disease. Tests to locate the SLN in CRC have started recently and so far there is no consensus on the method for its localization or its significance. The main aim of this study was to improve the tracing of SLN by using radioactive colloid. The secondary aims were to investigate the accuracy, sensitivity and rate of method’s identification. Especially important for the analysis is the significance of SLN and its correlation with other RLN.
Keywords: sentinel; colorectal cancer; lymph node; radioactive; colloid